The effectiveness of online learning during social distancing - rani lestari; Wantini Wantini (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study aims to investigate the causes of the online learning ineffectiveness at State Junior High School (SMPN) 3 Pendopo. The design of the study was a field research. The subjects of the study consisted of teachers, administrative staff, and students in grade 7 that were recruited using purposive sampling technique. The data were collected by conducting online interviews, observations, and data identification. Data were then analyzed using the inductive approach of Miles and Huberman, which included collecting data, reducing data, presenting data, and drawing conclusion. The results of the study showed that at SMPN 3 Pendopo, online learning system has not run well due to inefficient method, inadequate facilities and infrastructures, and students’ lack of awareness of the importance of online learning.